(3JQJjH dMSf GdYGeIs - (3CHh YHO Gddg Hf gGfF GdSHJis; (3eMeO Hf Ydj Hf gGfF, CHh YHO Gddg, GddNej, GdSHJj, GdZQfGWj,J (B733 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi NU gPg GdCeI HGddSGf GdYQHi hHYO aGdeGehd ai gPG Gdebhd GNJUGQ cJGH EfTGO hEQTGO GdSDGd ddCSJGP CHj YHO Gddg Hf gGfF GdSHJi , hgh GdPi QJH ajg dMf GdYGeI ddCSJGP GdfMhi CHj YHO Gddg Hf gTGe s
(3BNQgG (B:s
(3jJje hGdLeY CjJGe hjJGei bGd KYdH(B: (3GdjJje ai GdfGS ef bHd GdBHGA hgfG GfJgi eG ChQOJg hSejJg CHQGO GddBd , ef EfTGO GdVhGd , hEQTGO GdSDGd fLR GdebUhO hGdMeO ddg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdCNjQs
(3HgG GdJYbjHIs
(3LGA ai GdCYdGe Cfg eYLe UZjQ deaQOGJ ef GddZI hCSeGA GdHdOGf hZjQgGs
(3hgh GNJUGQ dJQJjH CHj YHO Gddg Hf gGfF GdSHJi dcJGH dMf GdYGeIs
(3dGHf gTGe GddNei s
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
Keywords: (3GddZIs